2021
DOI: 10.1038/s41598-021-92345-2
|View full text |Cite|
|
Sign up to set email alerts
|

High fructose and streptozotocin induced diabetic impairments are mitigated by Indirubin-3-hydrazone via downregulation of PKR pathway in Wistar rats

Abstract: Metabolic disorders are becoming more common in young population due to increased consumption of carbohydrate rich diet, lack of physical activity and stress. Fructose is used as a sweetener in many carbonated beverages and is a known inducer of oxidative stress and hypertension. Up-regulation of the double-stranded RNA-dependent protein kinase (PKR) causes impairment in insulin signaling pathway and metabolic dysfunctions in type 2 diabetes mellitus. In the present study we investigated the role of PKR and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Fructose (10%) ingestion for 6 weeks followed by streptozotocin administration (35 mg/kg) resulted in high blood glucose levels which altered locomotor function and increased oxidative and nitrative stress and inflammation in the striatum. A combination of fructose (10%) and low-dose STZ (35 mg/kg) is a well-known alternative model to induce major pathogeneses of T2D, insulin resistance, and partial pancreatic β -cell dysfunction in rats [ 34 , 35 ]. This model more closely resembles the later stages of T2D and has demonstrated a stable diabetic condition over an 11-week experimental period useful for chronic research studies as well as for routine pharmacological screening [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fructose (10%) ingestion for 6 weeks followed by streptozotocin administration (35 mg/kg) resulted in high blood glucose levels which altered locomotor function and increased oxidative and nitrative stress and inflammation in the striatum. A combination of fructose (10%) and low-dose STZ (35 mg/kg) is a well-known alternative model to induce major pathogeneses of T2D, insulin resistance, and partial pancreatic β -cell dysfunction in rats [ 34 , 35 ]. This model more closely resembles the later stages of T2D and has demonstrated a stable diabetic condition over an 11-week experimental period useful for chronic research studies as well as for routine pharmacological screening [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intraperitoneal injections of STZ, at low doses (35 mg/kg), were repeated every Monday for 6 weeks. Fructose (20%) in drinking water [ 61 ], combined with an HFD containing 34.9% (wt/wt) of fat (58Y1; Test Diet, Richmond, IN, USA), was applied to replace the rats’ regular diet (Rodent Laboratory Chow 5001, Purina, St. Louis, MO, USA). Tolbutamide (10 mg/kg, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Elevated glucose levels lead to the release of pro-inflammatory cytokines (interleukin (IL)-6, IL-18, pro-IL-1ß, and tumor necrosis factoralpha (TNF-α) [25,33,34]. Recent studies have shown that the STZ-induced T2DM animal model exhibits fibrosis and tissue damage, features of chronic inflammation [32,35]. Moreover, both in vitro and animal research have revealed that elevated blood glucose levels are a substantial factor in diabetes-induced myocardial fibrosis.…”
Section: Macrophages and Inflammation In Dcmmentioning
confidence: 99%